2019
DOI: 10.3390/ijerph16122239
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Anaerobic Digestion of Chicken Manure Under Gradually Elevated Organic Loading Rates

Abstract: Poultry manure is the main source of agricultural and rural non-point source pollution, and its effective disposal through anaerobic digestion (AD) is of great significance; meanwhile, the high nitrogen content of chicken manure makes it a typical feedstock for anaerobic digestion. The performance of chicken-manure-based AD at gradient organic loading rates (OLRs) in a continuous stirred tank reactor (CSTR) was investigated herein. The whole AD process was divided into five stages according to different OLRs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 43 publications
(50 reference statements)
1
16
0
Order By: Relevance
“…These nonpoint sources of pollution can be effectively controlled and remediated by cleaner production and green technologies. For instance, the manure and wastewater from livestock operation can be converted to bioenergy (e.g., biomethane) through various types of green technologies, such as anaerobic digestion [20,21]. With the combination of real-time monitoring system, the physico-chemical properties of the nonpoint source pollution can be efficiently determined to provide useful information for subsequent treatments and/or controls.…”
Section: Implications To Ensuring the Safety Of Irrigation Watermentioning
confidence: 99%
“…These nonpoint sources of pollution can be effectively controlled and remediated by cleaner production and green technologies. For instance, the manure and wastewater from livestock operation can be converted to bioenergy (e.g., biomethane) through various types of green technologies, such as anaerobic digestion [20,21]. With the combination of real-time monitoring system, the physico-chemical properties of the nonpoint source pollution can be efficiently determined to provide useful information for subsequent treatments and/or controls.…”
Section: Implications To Ensuring the Safety Of Irrigation Watermentioning
confidence: 99%
“…"The results showed that the biogas yield increased with increasing OLR, which was based on the volatile solids (VS), before reaching up to 11.5 g VS/(L•d), while the methane content was kept relatively stable and maintained at approximately 60%. However, when the VS was further increased to 11.5 g VS/(L•d), the total ammonia nitrogen (TAN), pH, and alkalinity (CaCO 3 ) rose to 2560 mg•L −1 , 8.2, and 15,000 mg•L −1 , respectively, while the volumetric biogas production rate (VBPR), methane content, and VS removal efficiency decreased to 0.30 L•(L•d) −1 , 45%, and 40%, respectively " [20].…”
Section: Introductionmentioning
confidence: 99%
“…The performance of chicken-manure-based AD at gradient organic loading rates (OLRs) in a continuous stirred tank reactor (CSTR) was investigated 150 days [20]. "The results showed that the biogas yield increased with increasing OLR, which was based on the volatile solids (VS), before reaching up to 11.5 g VS/(L•d), while the methane content was kept relatively stable and maintained at approximately 60%.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of protein-rich substrates, such as kitchen waste, poultry manure, microalgae, green legumes, oilseeds, etc. may lead to high concentrations of nitrogen (N) in the reactor during anaerobic digestion (AD) [1][2][3][4]. High concentrations of N inside the reactor negatively affect process stability and efficiency due to ammonia formation.…”
Section: Introductionmentioning
confidence: 99%